Applications of Organic Acids in Poultry Production: An Updated and Comprehensive Review - Wafaa A. Abd El-Ghany (Agriculture)
Feed additive antibiotics have been used for many decades as growth promotors or antibacterial substances worldwide. However, the adverse impacts of using antibiotics in animal or poultry feeds are not widely recognized. Therefore, the search for alternatives, such as probiotics, prebiotics, phytobiotics, post-biotics, bacteriophages, enzymes, essential oils, or organic acids (OAs), has become urgent. OAs are produced by beneficial intestinal bacteria through the fermentation of carbohydrates. OAs and their salts are still used as feed preservatives. They have long been added to feed in order to minimize contamination and the growth of harmful bacteria and fungi, reduce deterioration, and prolong the shelf life of feed commodities. Moreover, they have been mostly added to poultry feed as a blend to obtain maximal beneficial effects. The supplementation of poultry with OAs could improve the growth performance parameters and carcass traits, promote the utilization of nutrients, boost the immune response, and inhibit the growth of pathogenic bacteria. Therefore, this review article provides valuable insights into the potential benefits of using OAs in reducing microbial load, enhancing performance parameters in broilers and layers, improving gut health, and boosting the immune response.